STUDI POLA DAN KOLOKASI VERBA ATUR DAN ICA DALAM BAHASA BALI: KAJIAN BERBASIS KORPUS - Ida Wayan Eka Werdi Putra; I Made Rajeg (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This research aims to describe patterns and collocations between speech level of verbs atur and ica with personal pronouns in Balinese. The verbs atur and ica (along with their derivatives) and alus sor personal pronouns that filling the semantic roles of ACTOR and UNDERGOER, were selected as the sample and research variable boundaries based on Balinese speech levels. The data source is Balinese corpus that built from the Suara Saking Bali magazine issues 1-96. The method employed is a quantitative corpus analysis with statistical Chi-Square significance test (Χ²). The findings reveal that there is a close relationship between speech levels (anggah-ungguhing basa Bali) with the selection of verb lexicons and personal pronouns filling the roles of ACTOR and UNDERGOER in Balinese speech. The ACTOR role filled by alus sor personal pronouns shows a high collocational significance with the alus sor verb atur and its derivatives. On the other hand, the UNDERGOER role filled by alus sor personal pronouns demonstrates a high collocational significance with the alus singgih verb ica and its derivatives.